(untitled) (Research, Society and Development, 2022)
The growing demand for raw materials is driven by the growth of developing and emerging economies and represent the entire set of necessary and intrinsic products to the most varied production processes, extracted or obtained directly from Nature. These primary materials, which constitute the first stage in a process chain of essential transformations until obtaining a final product, are essential essences in growing demand, bearing in mind the emergence of developing economies and emerging technologies. This study presents the context in which the current excessive demand for these matters has led to their natural exhaustion. This panorama, associated with the difficulties caused by the limitations of commercial circuits caused by the Covid 19 Pandemic, is reflected in a devastating way in the manufacturing industries, directly affecting the economy. At the same time, there is a reflection on the importance of organic and non-organic waste that we all discard daily and where the most varied materials are found, which are often 100% reusable. Faced with this problem, there are limitations and difficulties in the creation of substances that replace raw materials, so the solution must involve recycling and reusing them.